Involvement of (pro)renin receptor in the glomerular filtration barrier - Ichihara, Atsuhiro (Springer-Verlag, 2008)
(Pro)renin receptor-bound prorenin not only causes the generation of angiotensin II via the nonproteolytic activation of prorenin, it also activates the receptor’s own intracellular signaling pathways independent of the generated angiotensin II. Within the kidneys, the (pro)renin receptor is not only present in the glomerular mesangium, it is also abundant in podocytes, which play an important role in the maintenance of the glomerular filtration barrier. Recent in vivo studies have demonstrated that the overexpression of the (pro)renin receptor to a degree similar to that observed in hypertensive rat kidneys leads to slowly progressive nephropathy with proteinuria. In addition, the handle region peptide, which acts as a decoy peptide and competitively inhibits the binding of prorenin to the receptor, is more beneficial than an angiotensin-converting enzyme inhibitor with regard to alleviating proteinuria and glomerulosclerosis in experimental animal models of diabetes and essential hypertension. Thus, the (pro)renin receptor may be upregulated in podocytes under hypertensive conditions and may contribute to the breakdown of the glomerular filtration barrier.